Reconstitution of contractile actomyosin rings in vesicles - Thomas Litschel (Nature Portfolio, 2021)
Cytoskeletal networks support and direct cell shape and guide intercellular transport, but relatively little is understood about the self-organization of cytoskeletal components on the scale of an entire cell. Here, authors use an in vitro system and observe the assembly of different types of actin networks and the condensation of membrane-bound actin into single rings.